Neuromodulation by selective angiotensin-converting enzyme 2 inhibitors - Pozdnyakova, Natalia; Krisanova, Natalia; Pastukhov, Artem; Tarasenko, Alla; Dudarenko, Marina; Chernykh, Anton; Pashenko, Alexander; Ryabukhin, Sergey; Tolstanova, Ganna; Volochnyuk, Dmitriy; Borisova, Tatiana (Neuroscience, 2022)
[Display omitted] •Neuromodulatory effects of ACE2 inhibitors were investigated in nerve terminals.•Two different types of small molecule ligands for selective ACE2 inhibition were tested.•EBC-36032 and EBC-36033 decreased exocytotic release of [3H]GABA.•Both inhibitors decreased the initial rate of uptake of L-[14C]glutamate and [3H]GABA.•Neurological side effects may be expected in therapeutic implementation. Here, neuromodulatory effects of selective angiotensin-converting enzyme 2 (ACE2) inhibitors were investigated. Two different types of small molecule ligands for ACE2 inhibition were selected using chemical genetic approach, they were synthesized using developed chemical method and tested using presynaptic rat brain nerve terminals (synaptosomes). EBC-36032 (1 µM) increased in a dose-dependent manner spontaneous and stimulated ROS generation in nerve terminals that was of non-mitochondrial origin. Another inhibitor EBC-36033 (MLN-4760) was inert regarding modulation of ROS generation. EBC-36032 and EBC-36033 (100 µM) did not modulate the exocytotic release of L-[14C]glutamate, whereas both inhibitors decreased the initial rate of uptake, but not accumulation (10 min) of L-[14C]glutamate by nerve terminals. EBC-36032 (100 µM) decreased the exocytotic release as well as the initial rate and accumulation of [3H]GABA by nerve terminals. EBC-36032 and EBC-36033 did not change the extracellular levels and transporter-mediated release of [3H]GABA and L-[14C]glutamate, and tonic leakage of [3H]GABA from nerve terminals. Therefore, synthesized selective ACE2 inhibitors decreased uptake of glutamate and GABA as well as exocytosis of GABA at the presynaptic level. The initial rate of glutamate uptake was the only parameter that was mitigated by both ACE2 inhibitors despite stereochemistry issues. In terms of ACE2-targeted antiviral/anti-SARS-CoV-2 and other therapies, novel ACE2 inhibitors should be checked on the subject of possible renin–angiotensin system (RAS)-independent neurological side effects.